2021
DOI: 10.3390/cells10061418
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the Heat Shock Protein A (HSPA) Family Potentiates the Anticancer Effects of Manumycin A

Abstract: Manumycin A (MA) is a well-tolerated natural antibiotic showing pleiotropic anticancer effects in various preclinical in vitro and in vivo models. Anticancer drugs may themselves act as stressors to induce the cellular adaptive mechanism that can minimize their cytotoxicity. Heat shock proteins (HSPs) as cytoprotective factors can counteract the deleterious effects of various stressful stimuli. In this study, we examined whether the anticancer effects of MA can be counteracted by the mechanism related to HSPs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 53 publications
1
5
0
Order By: Relevance
“…Li et al showed that the cell viability of LNCaP cells is reduced to 20% after treatment with 30 μM Manumycin A ( Li et al, 2014 ). Our findings are in line with that and with that of other studies showing IC 50 values in different cell lines between 4.3 and 50 µM Manumycin A ( She et al, 2005 ; Cho et al, 2015 ; Giudice et al, 2016 ; Kim et al, 2016 ; Sojka et al, 2021 ). Like Li et al, we were not able to induce a complete inhibition of cell growth, even when using concentrations of 100 μM Manumycin A.…”
Section: Discussionsupporting
confidence: 93%
“…Li et al showed that the cell viability of LNCaP cells is reduced to 20% after treatment with 30 μM Manumycin A ( Li et al, 2014 ). Our findings are in line with that and with that of other studies showing IC 50 values in different cell lines between 4.3 and 50 µM Manumycin A ( She et al, 2005 ; Cho et al, 2015 ; Giudice et al, 2016 ; Kim et al, 2016 ; Sojka et al, 2021 ). Like Li et al, we were not able to induce a complete inhibition of cell growth, even when using concentrations of 100 μM Manumycin A.…”
Section: Discussionsupporting
confidence: 93%
“…Therefore, our results suggest that increased loading of HSPA2 and HSPA1 into EVs may be a part of non-cell-autonomous mechanisms of proteostasis control upon proteotoxic stress. In this context, our previously published results 33,35 allow to speculate that HSPA paralogs could act in concert due to their high functional redundancy.…”
Section: Discussionmentioning
confidence: 92%
“…The in vitro model also indicated high HSPA6 expression inhibited the proliferation, migration and invasion of TNBC cell lines [ 30 ]. Besides, treating lung cancer cells with Manumycin A induced up-regulation of HSPA6, which could form a positive feedback loop and sensitize cancer cells to Manumycin A treatment [ 31 ]. On the contrast, one of the down-regulated DEGs OPN3 (ranks 16 of most down-regulated list) might be the potential oncogene target.…”
Section: Discussionmentioning
confidence: 99%